1987
DOI: 10.1007/bf00040950
|View full text |Cite
|
Sign up to set email alerts
|

Factors influencing in vitro multiplication and rooting of peach cultivars

Abstract: Success at propagating peach (Prunus persica (L.) Batsch) scion cultivars in vitro has been limited. This study describes factors influencing in vitro multiplication and rooting of 8 peach scion cultivars and one rootstock, as well as acclimatization and genetic stability of these cultivars. Shoot multiplication was best when 8.8/~M 6-benzylamino purine (BA) was added to the shoot proliferation medium. Maximum rooting occurred when shoots were placed on I/2-strength Murashige and Skoog (MS) medium, stored in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
41
1

Year Published

1987
1987
2017
2017

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 73 publications
(43 citation statements)
references
References 12 publications
1
41
1
Order By: Relevance
“…Antonopoulou et al (2004) reported the positive effect of a short period of darkness on the in vitro rooting. It has been reported that keeping cultures of Prunus cerasifera (Hammerschlag, 1982) and almond/peach hybrid rootstock Titan×Nemaguard (Channuntapipat et al 2003) in the dark prior to Transferring to light condition enhanced the rooting of explants. More effective photoreceptor activation is one of the factors which can be attributed to the positive effect of dark on rooting.…”
Section: Discussionmentioning
confidence: 99%
“…Antonopoulou et al (2004) reported the positive effect of a short period of darkness on the in vitro rooting. It has been reported that keeping cultures of Prunus cerasifera (Hammerschlag, 1982) and almond/peach hybrid rootstock Titan×Nemaguard (Channuntapipat et al 2003) in the dark prior to Transferring to light condition enhanced the rooting of explants. More effective photoreceptor activation is one of the factors which can be attributed to the positive effect of dark on rooting.…”
Section: Discussionmentioning
confidence: 99%
“…Similar results obtained in species cultured in liquid or low-agar concentration media is caused by greater availability of water (Bouniols 1974;Debergh 1983) and of nutrients (Debergh 1983;Singha 1982). This increased availability may be induced by a lower resistance to diffusion and closer contact between the explant and the culture medium (Hammerschlag 1982;Romberger and Tabor 1971;Singha 1982). Although sucrose is the most commonly used energy source for cultures in most of the propagation of woody species, reducing sugars like glucose that are not normally transported in sieve tubes, can be readily taken up and metabolized providing a better carbon source (Welander et al 1989).…”
mentioning
confidence: 99%
“…Some authors have reported that the time in in vitro culture could promote somaclonal variation (Hartmann et al 1989, Nayak andSen 1991), whereas Gould (1986) has reported that culture time does not seem to be the only parameter affecting genetic stability. Genetic variation in a culture line could be affected more by a genotype than by the period in culture (Hammerschlag et al 1987, Nayak and Sen 1998, Vendrame et al 1999.…”
Section: Discussionmentioning
confidence: 99%